2021
DOI: 10.3390/ma14174830
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Fibres as a Reinforcement of Gypsum Composites

Abstract: Three series of tests performed on fibre-reinforced gypsum composites are described herein. Sheep wool fibres and hemp fibres were used as reinforcement. The aim was to evaluate the capability of these biomaterials to enhance the fracture toughness of the gypsum matrix. The mechanical properties were measured by means of flexural tests on small specimens, whereas scanning electron microscopy with energy dispersive spectroscopy and X-ray diffraction were used to analyse the microstructure and composition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…This caused a reduction in the compressive strength of the composite which is in line with the previous studies. Compressive strength results of other studies about hemp fiber-reinforced gypsum plaster composite change from 5 MPa to 10 MPa which agree with previous results same as our study [12,[47][48][49]. However, the fiber-reinforced composite did not break into pieces during the test as it was compressed.…”
Section: Mechanical Characterization Of Compositessupporting
confidence: 91%
See 1 more Smart Citation
“…This caused a reduction in the compressive strength of the composite which is in line with the previous studies. Compressive strength results of other studies about hemp fiber-reinforced gypsum plaster composite change from 5 MPa to 10 MPa which agree with previous results same as our study [12,[47][48][49]. However, the fiber-reinforced composite did not break into pieces during the test as it was compressed.…”
Section: Mechanical Characterization Of Compositessupporting
confidence: 91%
“…Therefore, the tendency for eco-friendly construction materials is increased [10]. Natural fiber can be used as an additive material in construction materials like cement, concrete [11], gypsum plaster [12], and lime [13]. Eco-friendly materials play an important role in the market of building materials.…”
Section: Introductionmentioning
confidence: 99%
“…Their research demonstrated that the composite containing 5% wool and clay exhibited the lowest thermal conductivity and transmittance, indicating superior thermal insulation properties. The effect of sheep wool and hemp fibers on the mechanical properties of gypsum-based composites was studied by Fantilli et al [ 21 ]. They found that the addition of sheep wool and hemp fibers reduced the compressive and flexural strengths by approximately 20% compared to plain gypsum.…”
Section: Introductionmentioning
confidence: 99%
“…To tailor the initial setting time and bolster the mechanical strength of gypsum materials, significant research has focused on their modification, such as the incorporation of organic polymers and inorganic additives into gypsum systems [8][9][10][11][12][13]. Yu et al notably enhanced the toughness and strength of composites by integrating organic and inorganic units at a molecular scale into an inorganic base [14].…”
Section: Introductionmentioning
confidence: 99%